2016
DOI: 10.4314/acsj.v24i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Nature of resistance of cowpea <I>Alectra vogelii</I> infestation

Abstract: Alectra vogelii (benth) is parasitic weed which causes significant yield reductions in cowpea (Vigna unguiculataWalp) in Africa. The objective of this study was to identify the type of gene action controlling the trait for resistance to Alectra vogelii in cowpea and estimate the heritability of the trait. Seven genotypes of cowpea were mated in half diallel and their F 2 progeny, including parents, were evaluated for reaction to Alectra vogelii infection in the field in two locations at Ilonga and Hombolo Agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The results showed that both additive or/and non-additive genes effects were involved in the expression of all the investigated traits. Mbwando et al (2016) also claimed the existence of additive and nonadditive gene actions in cowpea resistance to Alectra parameters. The proportion of additive gene effects was more important for SEV and HSW with 2σ 2 GCA / (2σ 2 GCA +σ 2 SCA ) values more than unity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that both additive or/and non-additive genes effects were involved in the expression of all the investigated traits. Mbwando et al (2016) also claimed the existence of additive and nonadditive gene actions in cowpea resistance to Alectra parameters. The proportion of additive gene effects was more important for SEV and HSW with 2σ 2 GCA / (2σ 2 GCA +σ 2 SCA ) values more than unity.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have been undertaken to investigate gene actions involved in cowpea resistance to Alectra vogelii. Mbwando et al (2016) studied the genetic factors involved in cowpea resistance to Alectra for two parameters (number of Alectra shoots emerged and number of cowpea plant infested). The outcome of this study showed medium narrow sense heritability for each trait, 41.28% and 44.39% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Though this genotype may not be recommended as being desirable, it may find its usefulness in molecular mapping studies. Such a genotype (G2) can be crossed with a relatively high yielding genotype (such as G27) to create a mapping population to utilise in QTL associated tagging for seed cotton yield [7,15]. AMMI evaluation of environment performance, Masumba was the best performing environment followed by Magoye with average seed co yield of 1249 kg/ha and 731 kg/ha The high performance of this area could be attributed to a roundup favourable environment in the area i.e temperature, rainfall amount, type of…”
Section: M1-first Mega Environment M2-second Mega Environment and M3 Cross Symbol Environmentsmentioning
confidence: 99%
“…Identifying desirable high yielding genotypes is key in improving SCY. Previous authors have suggested the use of molecular marker-assisted selection in selecting for desirable genotypes, as they are independent of the environmental effect [6,7]. However, in this study we tend to explore the phenotypic performance (P) taking into consideration genetic make-up (G), various environments (E) subjected to, and the genotype x environmental interaction (GEI).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that selection and utilisation of heat tolerant genotypes is the most feasible way to reduce yield losses in maize [9]. Selection of desirable genotype, where one or two variables (traits) are involved, has been achieved using visual selection and or by genotypic trait analysis [10,11]. On the other hand, multivariate analysis such as principle component analysis (PCA) have been used where genotypic selection relies on genotypic response of several traits [12].…”
Section: Introductionmentioning
confidence: 99%